Cognitive Engagement and Technology: The Influence of Wolfram Alpha in Mathematics Education - Neupane, Janak Prasad; Upadhyaya, Hari Prasad; Kharel, Binita (Annual Oxford Journal, 2025)
Student cognitive engagement is a multidimensional construct that predicts students’ academic performance. In this context, the role of educational technology in enhancing students’ cognitive engagement is a major concern among mathematics teachers, educators, and researchers in mathematics education. The purpose of this study was to investigate the effect of using Wolfram Alpha as a teaching and learning tool in mathematics on the cognitive engagement of secondary-level students. The quasi-experimental method with a Pretest-Posttest Non-equivalent Group Design was used to fulfill the purpose of the study. Sixty-four class 11 students studying mathematics from two institutional schools of Butwal Sub metropolitan city were the participants of the study. The study utilized adapted questionnaires: Cognitive Engagement Scale Extended Version (CSE-E) and Students’ Opinion Scale (SOS) from earlier studies, with little modification for this context. The independent t-test and ordinal logistic regression analysis were used to analyze the data. The study findings reveal that students who received Wolfram Alpha in teaching and learning have higher cognitive engagement as compared to those who do not receive it. Thus, it is concluded that teaching and learning mathematics using Wolfram Alpha positively impacts students’ cognitive engagement. Findings from this study enlighten mathematics teachers, educators, and researchers in enhancing the cognitive engagement of students through the use of Wolfram Alpha in teaching and learning mathematics.